2010
DOI: 10.1097/tp.0b013e3181c9dc7d
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Transplantation Temporarily Improves Pancreatic Function in Streptozotocin-Induced Diabetes: Potential Involvement of Very Small Embryonic-Like Cells

Abstract: BACKGROUND The role of bone marrow (BM)-derived cells in pancreatic β-cell regeneration remains unresolved. Here we examined whether BM-derived cells are recruited to the site of moderate pancreatic injury and contribute to β-cell regeneration. METHODS Low-dose streptozotocin (STZ) treatment was utilized to induce moderate pancreatic damage and hyperglycemia. Enhanced green fluorescent protein-positive (EGFP+) BM chimeras were evaluated for β-cell regeneration after STZ treatment. RESULTS To test the hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 55 publications
(65 reference statements)
2
39
0
Order By: Relevance
“…Their presence amongst the MSCs in the Wharton's jelly is in agreement with observations made by other groups that MSCs contain a sub-population of more primitive stem cells [52] or even as postulated by Taichman and group [53] that VSELs are precursors of MSCs. Various studies have also reported that VSELs are mobilized into peripheral blood in response to injury/ stress in animal models [27,[54][55][56] as well as in humans [28][29][30]57] -thus suggesting a role in regeneration and homeostasis.…”
Section: Developmental Origin Of Vselsmentioning
confidence: 99%
“…Their presence amongst the MSCs in the Wharton's jelly is in agreement with observations made by other groups that MSCs contain a sub-population of more primitive stem cells [52] or even as postulated by Taichman and group [53] that VSELs are precursors of MSCs. Various studies have also reported that VSELs are mobilized into peripheral blood in response to injury/ stress in animal models [27,[54][55][56] as well as in humans [28][29][30]57] -thus suggesting a role in regeneration and homeostasis.…”
Section: Developmental Origin Of Vselsmentioning
confidence: 99%
“…The ability of such cells to selectively home to damaged tissues has been variously linked to their expression of L-selectin [50] , β2-integrins [51] and stromal cell-derived factor-1 [52] . In some studies, a direct trans-differentiation of bone marrow-, a direct trans-differentiation of bone marrowa direct trans-differentiation of bone marrowderived stem cells into insulin-positive β-cells was demonstrated, either in vivo or following in vitro lineage manipulation [53][54][55] but the direct contribution of bone marrow stem cells to new β-cells has generally been found to be low and inconsistent with the resulting increase in insulin secretion and/or normalization of blood glucose [46,[56][57][58] .…”
Section: Bone Marrow Stem Cells and β-Cell Regenerationmentioning
confidence: 99%
“…Controversial evidence on neogenesis of insulinproducing cells has been presented by studies using hematopoietic progenitor markers such as SCA-1 and ckit, ranging from positive identification of differentiation (22,46) to negative results (19,68). The positive identification of Fr25lin − cell conversion to produce insulin (24) was used to address the possible use of these markers for prospective identification of the candidate stem cells that participate in islet regeneration.…”
Section: Hematopoietic Progenitor Markers Do Not Delineate Islet-engrmentioning
confidence: 99%
“…This established model (8,14,19,22,24,25,40,64,68) includes selective injury by five consecutive doses of 60 mg/g STZ (days −6 to −2) followed by sublethal irradiation (675 rad) and cell grafting after 1 day (Fig. 2A).…”
Section: Differential Effects Of Cell Subsets On Recovery From Chemicmentioning
confidence: 99%
See 1 more Smart Citation